A Golgi study of neurons in the camel cerebellum (Camelus dromedarius) - Saleh M. Al‐Hussain (14777053) (2023)
Neurons in the cerebellar cortex of camels were studied using modified Golgi impregnation methods. Neurons were classified according to their position, morphology of their soma, density and distribution of dendrites, and the course of their axons. Accordingly, eight types of neurons were identified. Three types were found in the molecular layer: upper and lower stellate cells and basket cells, and four types were found in the granular layer: granule cells, Golgi Type II cells, Lugaro cells, and unipolar brush cells. Only the somata of Purkinje cells were found in the Purkinje cell layer. The molecular layer is characterized by the presence of more dendrites, dendritic spines, and transverse fibers. Golgi cells also show extensive dendritic branching and spines. The results illustrate the neuronal features of the camel cerebellum as a large mammal living in harsh environmental conditions. These findings should contribute to advancing our understanding of species-comparative anatomy in achieving better coordination of motor activity.  Other Information Published in: The Anatomical Record License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/ar.24742